Prevalence and Associated Factors with Sugar-sweetened Beverages Consumption among Kurdish High-school Children - Deldar Morad Abdulah; Saad Jbraeil Sulaiman; Ayoub Abid Abdulmajeed (Indian Journal of Community Medicine)
Adolescents’ excessive consumption of sugar-sweetened beverages (SSBs) has become a global concern due to its detrimental effects on health. We explored the prevalence and associated factors of the consumption of SSB in high-school children in the Kurdistan Region. In this study, we included 560 students randomly from the 152 available high schools in Duhok City in the Kurdistan Region. Both genders of high school children who registered for the academic years 2021–2022 in 32 high schools were eligible. The study found that a considerable number of students did not eat breakfast (32.68%). Mostly, the students had lunch (83.21%) and dinner (53.57%), with 53.57% having extra eating portions. A significant percentage of the students consumed junk food (fast food) more than three times per week (39.82%) and consumed SSB 1–3 times/day (61.07%) at varying frequencies. The study found that 14.64% and 12.86% were overweight and obese, respectively. The prevalence of SSB consumption 4–5 times/week was 47.68% (soda), 21.61% (tea), 34.64% (coffee), 22.50% (energy drink), and 36.25% (juice). A similar prevalence of SSB consumption was found among parents (23.39%) and friends/classmates (20.36%). The male students were more likely to consume tea (P = 0.0104). However, female students were more likely to consume juice and energy drinks (P = 0.004 and P < 0.0001, respectively). Students with lower levels of education were also more likely to consume SSB. The intake of SSB was high among high school children in the Kurdistan Region and was related to gender and parents’ consumption.